A high-dose rapamycin treatment alleviates hepatopulmonary syndrome in cirrhotic rats. Issue 1 (January 2020) - Chang, Ching-Chih; Chuang, Chiao-Lin; Hsin, I-Fang; Hsu, Shao-Jung; Huang, Hui-Chun; Lee, Fa-Yauh; Lee, Shou-Dong
Abstract : Background: Rapamycin is a type of immunosuppressive agent that acts through inhibition of mammalian target of rapamycin (mTOR). Hepatopulmonary syndrome (HPS) is a lethal complication in cirrhotic patients. It is characterized by hypoxia and increased intrapulmonary shunts, in which pulmonary inflammation and angiogenesis play important roles. The current study aimed to evaluate the effect of rapamycin on HPS using the experimental model of common bile duct ligation (CBDL)-induced cirrhosis in rats. Methods: The rats received low-dose (0.5 mg/kg), high-dose (2 mg/kg) rapamycin, or vehicle from the 15th to the 28th day post CBDL. Then the mortality rate, hemodynamics, biochemistry parameters, arterial blood gas and plasma levels of vascular endothelial growth factor (VEGF) and tumor necrosis factor (TNF)-α were evaluated on the 28th day post CBDL. Pulmonary histopathological stains were performed, and protein expression was examined. In parallel groups, the intrapulmonary shunts of CBDL rats were measured. Results: Compared with the control, a high-dose rapamycin treatment decreased portal pressure and improved hypoxia in CBDL rats. It also reduced the plasma level of VEGF and TNF-α and decreased intrapulmonary shunts. Meanwhile, it ameliorated pulmonary inflammation and angiogenesis and downregulated the protein expression of mTOR, P70S6K, nuclear factor kappa B (NFκB), VEGF, and VEGF receptor 2. In contrast, low-dose rapamycin did not attenuate intrapulmonary shunts despite ameliorating portal hypertension. Conclusion: High-dose rapamycin ameliorates HPS in cirrhotic rats as evidenced by the alleviated hypoxia and decreased intrapulmonary shunts. Downregulation of the mTOR/P70S6K, NFκB, and VEGF signaling pathways might play a key role.